Impact of respiratory motion on lung dose during total marrow irradiation - Kavak, Ayse Gulbin; Surucu, Murat; Ahn, Kang-Hyun; Pearson, Erik; Aydogan, Bulent (Frontiers in Oncology, 2022)
We evaluated the impact of respiratory motion on the lung dose during linac-based intensity modulated TMI (IMTMI) using two different approaches: 1) measurement of doses within the lungs of an anthropomorphic phantom using thermoluminescent detectors (TLD) and 2) treatment delivery measurements using ArcCHECK where gamma passing rates (GPR) and the mean lung doses were calculated and compared with and without motion. In the first approach, respiratory motions were simulated using a programmable motion platform by using typical published peak-to-peak motion amplitudes of 5, 8, and 12 mm in craniocaudal (CC) direction, denoted here as M1, M2, and M3 respectively, with 2 mm in both anteroposterior (AP) and lateral (LAT) directions. TLDs were placed in five selected locations in the lungs of a RANDO phantom. Average TLD measurements obtained with motion were normalized to that obtained with static phantom delivery. The mean dose ratios were 1.01 (0.98-1.03), 1.04 (1.01-1.09), and 1.08 (1.04-1.12) for respiratory motions M1, M2, and M3, respectively. In the second experimental approach, we evaluated an extreme case of breathing with 15 mm motion only in CC direction. We placed an ArcCHECK device on a commercial motion platform and delivered the clinical IMTMI plans of 5 patients. We compared, with and without motion, the dose volume histograms (DVH) and mean lung dose calculated with the ArcCHECK-3DVH tool as well as gamma passing rate (GPR) with 3%, 5%, and 10% dose agreements and a 3mm constant distance to agreement (DTA). GPR differed by 11.1±2.1% and 3.8±1.5% 0.1±0.2 with dose agreement criteria of 3%, 5%, and 10%, respectively. This indicates that respiratory motion impacts dose distribution in small and isolated parts of the lungs. More importantly, the impact of respiratory motion on the mean lung dose, a critical indicator for toxicity in TMI, was not statistically significant (p>0.05) based on the Student’s t-test. We conclude that most patients treated with IMTMI will have negligible dose uncertainty due to respiratory motion. This is particularly reassuring as lung toxicity is the main concern for future IMTMI dose escalation studies.